Clinical evaluation of asthmatic children and adolescents: relevance of interdisciplinary attention - Karina Machado Siqueira; Geovanna Líscio Pereira; André Luiz Bittencourt; Camila Silva Colodino; Isabela Cristine Ferreira Fernandes; Maria Alves Barbosa (Universidade Federal de Goias, 2015)
Descriptive, retrospective study, aimed to evaluate clinical conditions of asthmatic children and adolescents at the beginning of treatment and after six months of accompaniment by a multi-professional team, focused on interdisciplinary attention. A research developed in a reference ambulatory for tertiary attention of infant asthma, in Goiânia, Goiás, Brazil. Data was collected from 101 medical records from January and March 2013. Children and adolescents were predominantly male (70,3%), aged between two and five years (31,7%) and clinically classified as moderated persistent asthma (47,6%). After following them for six months, it was seen that most (64,4%) obtained total or partial control of the disease, reduction of all symptoms identified in the first consultation and presented high adherence to the proposed pharmacological treatment (70,3%). Interdisciplinary attention can result in improved clinical control and contribute to advances in assistance quality to asthmatic children and adolescents.